2020
DOI: 10.3389/fnins.2020.580205
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Wall Enhancement Analyses in Unruptured Aneurysms Are Associated With an Increased Risk of Aneurysm Instability

Abstract: ObjectiveIntracranial aneurysm wall enhancement (AWE) is independently associated with unstable aneurysms. However, a quantitative analysis of wall enhancement is lacking. This study aims to investigate the relationship between qualitative and quantitative wall enhancement indices (WEIs), traditional risk factors for aneurysms, and clinical ELAPSS/PHASES scores in a large cohort of intracranial saccular aneurysms.Materials and MethodsIn this cross-sectional study, a total of 174 patients (mean age 60.4 ± 9.5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, in this study the PS exhibited an avid uptake of Gd in T1 + Gd images, which is suboptimal when analyzing specific AWE (SAWE). Other studies have successfully used white matter structures for normalization of enhancement through pre/post Gd indices 9 , 13 , 32 . After multiple comparisons and detailed histogram analysis, normalization to the CC resulted in a more reliable parameter in determining AWE.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study the PS exhibited an avid uptake of Gd in T1 + Gd images, which is suboptimal when analyzing specific AWE (SAWE). Other studies have successfully used white matter structures for normalization of enhancement through pre/post Gd indices 9 , 13 , 32 . After multiple comparisons and detailed histogram analysis, normalization to the CC resulted in a more reliable parameter in determining AWE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that AWE could be a biomarker of vessel wall inflammation in unstable IAs prone to evolve toward rupture (86). Indeed, some studies performed on unruptured IAs demonstrated a correlation between AWE and common risk factors of IA rupture such as a larger size (≥7 mm), an irregular shape, a high aspect ratio (depth/neck width) and its localization in the anterior cerebral, posterior communicating and posterior cerebral arteries (87)(88)(89)(90)(91). A correlation between AWE intensity and the severity of PHASES and ELAPSS scores has also been demonstrated (92).…”
Section: Inflammation Imagingmentioning
confidence: 99%
“…In addition, there is no consensus on the definition of AWE as some studies included both FAWE and CAWE whereas others only studied CAWE. Most studies qualitatively assessed AWE inducing a lack of reproducibility, therefore quantitative AWE measurement should be considered ( 91 ). Finally, there is a heterogeneity concerning the definition of unstable IA qualified as growth, morphology changes, symptomatic and/or rupture ( 97 ).…”
Section: Inflammation Imagingmentioning
confidence: 99%
“…Presence of AWE has been correlated to anatomical characteristics of IAs such as size, location, and shape [ 52 , 65 , 70 , 73 , 76 , 100 , 108 , 109 ]. AWE is described to be higher in larger IAs [ 65 , 73 , 76 ].…”
Section: High-resolution Vessel Wall Magnetic Resonance Imaging To Ev...mentioning
confidence: 99%